A Comparative Study on: the Aspects of Imagination in the Text and Paintings of Nezami’s Khosrow and Shirin (Based on Gilbert Durand Hypothesis) - Farimah Pourmand; Bita Mesbah (مطالعات زبانی و بلاغی)
Reverie imagination used in the lyrics can be traced in mythological and cultural collective unconscious. The contradiction of good and evil in the romantic story of Khosrow and Shirin, converts the central theme of the story into a heroic one. These heroic concepts can be recognized by using the formula of Gilbert Durand’s method in configuring aspects of human imagination. The nature of image is at the central point of Durand’s thought, and the binary structural base he points is dynamited at the outset by the possibilities of the ternary. Durand’s method deals with the structure of the human imaginary, within which it stablishes a typology of figures, and organized according to several central archetypes. Thus he postulates two main orders of image, the diurnal and nocturnal, corresponding to two general types of imagination. The Diurnal Order is characterized as diuretic, whereas the Nocturnal Order is to be found two subgroupings: the synthetic and the mystical. These categories are underpinned by the reflex dominants. It uses the human reflexes (postural, digestive and sexual) as material for its demonstration, and examples taken from the mythological collective unconscious. The analysis is based on 6 distinguished paintings related to the books of Khamsa which were designed during the Timurid’s era. So, the research is comparing the pictorial methods used in the paintings to show the imaginative characteristics of the story with the imaginative phenomena’s in the text of the story. Analyzing the text shows, the usage of different diurnal and nocturnal symbols such as: death, ascension, dagger, killing, water, dripping, bloodthirsty, trembling, anger, and so on. In the paintings, the artist uses some of these symbols like dripping, death, dagger and etc. In order to achieve the imaginary boundaries of imagination the poet encompasses, some other visual techniques helped the artist, like: the use of vertical and horizontal axes with positive and negative values as well as dividing the image into two parts with some pictures that have positive and negative evaluations. Finally, the results show that the painters are totally depended on the poet’s aspects of imagination especially in the basic elements and descriptions of the principals and essentials of the story in the text. But also, in order to compensate the limitations of painting, they used new technical painting methods which in some cases are further than imaginative.